(untitled) (Journal of the College of Basic Education, 2022)
The study will attempt to search for the content of Russian sources, especially the documentary ones, which mentioned Muscat in its historical records that included many years of modern history, and try to monitor and follow up what was written down by Russian travelers and sailors, as well as by consuls and natural scientists, of information related to Muscat in terms of geography, trade and its political conditions. At a historical stage marked by the existence of competition between Britain and the Ottoman Empire over the Arabian Gulf, and another between the former and each of Russia and Germany, in an attempt by each party to extend its influence at the expense of the other party.